PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DISERTAI KUIS TEKA TEKI SILANG (TTS) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMPN 3 BONJOL KAB. PASAMAN TAHUN PELAJARAN 2013/2014 - Fitriani, Yetti - (STKIP PGRI Sumbar, 2014)
The studentsâ learning score at class VIII SMPN 3 Bonjol is stiil disappointed that are seen from average of activity test about blood circulation system of human year 2012/2013 which is low score in below minimal pass criteria. One of cause are low the studentsâ score, because it is least hopes and motivation of student in teaching learning process, the students is least active at class. The purpose of the research is to see the effect of cooperative learning model type Numbered Head Together (NHT) with crossword quiz toward the studentsâ biology score at Class VIII SMPN 3 Bonjol. Kinds of the research are experiment and population is all of class VIII SMPN 3 Bonjol that is register of year 2013/2014 Bonjol. The design of research is Randomized Control Group Posttest Only Design. SMPN 3 Bonjol still has 2 classes, so giving the sample is done using Total Sampling. Instruments are used writing test with objective test. The date analysis is done with t exam. Based test score of learning biology students which is got average score of experiment 81.79 and average score of control 74.63. the result of data analysis of exam t that tcalculate (3.15) > ttable (1.67) that hypothesis is accepted. Based the result of research can be concluded that the effect of cooperative learning model type Numbered Head Together (NHT) with crossword quiz toward the studentsâ biology score at Class VIII SMPN 3 Bonjol of year 2013/2014 about blood circulation system of human.